Topographical and structure-soil-structure interaction effects on dynamic behavior of shear-wall buildings on coastal scarp. (15th November 2021) - Sucasaca, Julio; Sáez, Esteban
Highlights: We investigated the influence of slope topography on DSSI between close shear-wall buildings. A numerical model based on real buildings taken as cases for this study. We concluded that the surface profile has a large effect on the dynamic response of a stiff building. DSSSI has negligible additional effect from a practical point of view with respect to DSSI. Results suggest that the design of low-rise buildings located near a slope crest should be cautious. Abstract: This paper investigates numerically the influence of slope topography, soil stratigraphy and dynamic interaction between close shear-wall buildings of typical residential projects on coastal scarp. A numerical model based on real buildings taken as cases for this study, is calibrated with field measurements. A nonlinear finite element dynamic analysis is conducted to derive topographical aggravation factors prior to excavation and construction of the buildings and to assess structural responses after their construction for different interaction scenarios and ground motion inputs. We concluded that the surface profile has a large effect on the dynamic response of a stiff low-rise building when their characteristic wavelengths are close each other and it can play a detrimental role increasing up to 80% the interstory drift, 35% the seismic coefficient and 57% the fixed-base fundamental period depending on the input. In several other input cases including far-field earthquake records, dynamic soil-structure interaction is beneficial. Furthermore, it is shown that the structure-soil-structure scenario has negligible additional effect from a practical point of view with respect to soil-structure interaction for this case of study. These results suggest that similar residential projects should be cautious in the design of low-rise buildings located near a slope crest.